Accounting Standards and Insurer Solvency Assessment - Windsor, Peter; Chong-Tai Bell, Michelle; Yong, Jeffery (Washington, D.C. : International Monetary Fund, 2020)
The paper explores the use of accounting standards for insurer solvency assessment in the context of the implementation of IFRS 17. The paper is based on the results of a survey of 20 insurance supervisors. Overall, IFRS 17 is a welcome development but there will be challenges of implementation. Not many insurance supervisors currently intend to use IFRS 17 as a basis for solvency assessment of insurers. Perceived shortcomings can be overcome by supervisors providing clear specifications where the principles-based standard allows a range of approaches. Accounting standards can provide a ready-made valuation framework for supervisors developing new solvency frameworks.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet